Inclusive Education Management: A Systematic Review of Practices, Challenges, and Solutions in Educational Institutions - Wiwik Dyah Aryani; Oki Dermawan; Saim Kayadibi; Zohaib Hassan Sain (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
Inclusive education management aims to ensure equitable access to learning for all students, including those with special needs. Despite broad policy support, implementation remains uneven across contexts, including Indonesia. Common barriers include constrained resources, insufficient teacher preparation, cultural resistance, and high teacher workloads. This study conducts a systematic literature review (SLR) to synthesize recent evidence on practices, challenges, and solutions. The analysis identifies effective practices such as comprehensive teacher professional development, provision of disability-friendly facilities, and sustained collaboration among schools, families, and communities. Persistent constraints include budget limitations, inadequate psychosocial support, and social stigma that hinders the inclusion of students with special needs in mainstream classrooms. To organize actionable responses, the review integrates management perspectives from Total Quality Management, distributed leadership, and change theory, providing a structured pathway for improvement. Based on these insights, the paper recommends strengthening inclusive education policies, leveraging educational technologies, and implementing public awareness initiatives to build acceptance. Overall, the findings highlight the need for coordinated, long-term commitments by governments, schools, and communities to achieve a fair and inclusive education system.